Comparative Quality Analysis between Tap Water and Bottled Water: A Case Study of Koya City in Iraq - Muhammad, Hanaa A.; Sediq, Khalid N.; Sdiq, Kwestan H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
Recently, bottled water consumption has been increasing significantly, even when the quality of tap water is considered excellent, which contributes to plastic pollution. Besides, reducing the use of plastic generally is recommended world widely, as its consumption is in an alarming rate. Therefore, this study aims to compare the tap and bottled water and manifest the reasons behind choosing the bottled water, which is less comfortable and often more expensive over the tap water. In this study, samples have been taken from both bottled and tap water in Koya city from November 2020 to May 2021 to test their quality using PH, DO, EC, and TDS meter, hardness was determined by complexometric titration method at 21°C, and XRF spectrometers. According to the quality standards, most of the variables were in a permissible range, except for dissolved oxygen and Aluminum content in both types of water and TDS for two types of bottled water. However, the quality of tap water was much safer to be used, as compared with the bottled water.